PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE STAD TERHADAP PENANAMAN MORAL CINTA TANAH AIR DI KELAS 4 SEKOLAH DASAR - Stelawati, Yuyun; Shokib Rondli, Wawan; Aditia Ismaya, Erik (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research was motivated by the student’s low moral level of love for the country at SD Pati Lor 02. The problem in this research was that many students did not know the true meaning of love for one's country. The aim of the research was to find out whether there were differences in students' problem solving abilities in the material on cultivating moral love for the country in class IV at SD Pati Lor 02 using the STAD type cooperative learning model. The type of research used was Pre-Experimental Design quantitative research with an experimental class of 33 students. Data collection techniques include interviews, tests (pretest and posttest) and documentation. The data analysis used is initial analysis using normality testing and hypothesis testing. Final data analysis uses paired sample T-test and N-Gain statistics. The analysis technique uses a t-test (paired sample t-test). The results obtained show a tcount of 3.6745 with a significance of 0.00. It is said to be significant if n < 0.05, this shows that n = 0.00, meaning n is smaller than the significance of 0.05, meaning that H0 is rejected and Ha is accepted, which means that there is a significant difference between the average values ​​before treatment (pretest). with the average value after treatment (post-test). The result of the N-Gain value is 0.51, indicating that there is an increase in students' problem solving abilities in learning using the STAD type cooperative learning model reaching medium criteria.